Assessment of climate awareness, policy development, and action across Nigerian states - Okereke, Chukwumerije; Okoh, Sadiq; Ogenyi, Timothy; Olorunfemi, Gboyega (Frontiers in Climate, 2025)
IntroductionAs climate governance increasingly adopts multilevel approaches, subnational actors play a central role in achieving national and global climate objectives. However, in Nigeria, as in many other developing countries, the role of subnational actors in climate governance remains underexplored. Understanding their institutional readiness is crucial for meeting national climate commitments, including the 2060 net-zero target. This paper presents the first comprehensive assessment of climate awareness, policy, and action across all 36 Nigerian states.MethodsUsing a mixed-methods design, the study combined document and budget reviews, a national survey of 1,306 respondents from relevant ministries and agencies, and a stakeholder validation workshop with over 600 participants. Indicators examined included climate literacy, policy presence and alignment, budgetary commitments, and inter-agency coordination.ResultsFindings reveal low climate knowledge among subnational officials, weak public awareness, and limited policy development. Only a handful of states, possess climate policies or action plans, and fewer than 20% have climate-related budget lines. Cross-sectoral collaboration and alignment with national frameworks are also weak.DiscussionThese gaps expose structural and institutional weaknesses that undermine Nigeria’s multilevel climate governance. Achieving the 2060 net-zero goal requires harmonized subnational frameworks, enhanced capacity-building, and innovative tools—such as performance-based disclosure and rating systems—to incentivize accountability and stimulate stronger state-level climate action. Positioned within debates on multilevel governance, the study highlights Nigeria as a critical test case of how federated system in the Global South can recalibrate institutions to transform symbolic commitments into substantive action.